14. mezinárodní vědecká konference Didaktická konference 2021 Sborník příspěvků - Viselga, Gintas (Masaryk University Press, 2021)
Title in English: 14th International Scientific Conference Didactic Conference 2021: Proceedings Didactics of mathematics, natural sciences and vocational education represent developing areas and are a breeding ground for new ideas and approaches. In mathematics and physics, the proceedings provide an overview of the historical development of education process and the possibilities of activating students. From a practical point of view, physics and chemistry are interconnected by using simulations in teaching. Vocational education is represented from various perspectives, whether in technical education, by solving logistical problems, or educational activities in the teaching of economic subjects. Due to the current situation, there are abundant contributions on the effects of the ongoing pandemic on the educational process and distance learning.